APPLICATION OF HAND MASSAGE THERAPY TOWARDS PAIN LEVEL IN PATIENTS POST HEART CATETERIZATION AT DR M DJAMIL PADANG - Putri Dafriani; Helena Patricia; Dian Dedi Priyadi; Weni Sartiwi (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Cardiovascular disease is one of the leading causes of death in Indonesia. One way to overcome and treat heart disease is cardiac catheterization. The effect of cardiac catheterization is pain. One of pain management is hand massage. The purpose of this study was to determine the effect of hand massage therapy on pain levels in post cardiac catheterization patients at Dr M Djamil Hospital Padang in 2021. The type of research was Quasy Experimental design Two Group Pretest-Posttest. The data were collected 12-25 February 2021. The population were patients after cardiac catheterization. Sampling technique was purposive sampling. The total sample was 20 patients. We divided into 2 groups, intervention and control group. The data were processed by univariate and bivariate analysis using the Mann Whitney-U test. The results of the intervention group study obtained an average pre-test pain intensity of 5.8 and post-test 2.9. Meanwhile, in the control group, the pre-test scores were 5.7 and the post-test scores were 5.7. Statistical test results obtained p value = 0.000 <0.05. It can be concluded that there was an effect of hand massage therapy on pain levels in post cardiac catheterization. Nurses expected to apply hand massage therapy in reducing pain.